(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the international relations of the Republic of Uzbekistan with France and Germany. It explores areas of cooperation in the fields of politics, economy, culture, education, and science. France and Germany are considered key strategic partners of Uzbekistan in Europe. The article presents information on major investment projects, cultural exchanges, educational programs, and technical assistance initiatives implemented in collaboration with these countries. It also discusses official state visits, bilateral agreements, and prospective directions for future cooperation.